ACTIVISM AND PRAGMATISM: CHALLENGES FACING THE HUMAN RIGHTS COMMITTEE IN ENSURING INDONESIA’S FULFILLMENT OF ITS ICCPR OBLIGATIONS - Muhammad Raihan Sjahputra (Mimbar Hukum, 2023)
Abstract As a state party to the ICCPR, Indonesia is subject to the compliance monitoring procedures enacted by the Covenant, which include, inter alia, the submission of State reports to the Human Rights Committee (HRC) as its treaty body and the obligation to comply with the recommendations made by the Committee as the output of the review process of said State report. Such procedures are enacted in the hopes of ensuring the States parties’ compliance with the treaty obligations. However, based on the judgement of the HRC themselves, as reflected in their Concluding Observation on Indonesia’s Initial State Report, it can be inferred that there are certain issues which demonstrate Indonesia’s failure to fulfill their ICCPR obligations, which to this day still persists. This article intends to delve on discussions regarding the factors that may be the cause of said failures, and finds that there are at least two such factors, which are the unwarranted expansion of treaty obligations towards its States parties by the HRC themselves, and an inhibition of a more pragmatic nature in the form of political reluctance by Indonesia as the State party in question themselves to follow the HRC’s recommendations due to the lack of internal will and external pressure. Abstrak Sebagai salah satu negara anggota ICCPR, Indonesia memiliki kewajiban untuk mematuhi prosedur-prosedur pengawasan kepatuhan yang diatur dalam ICCPR itu sendiri, yang meliputi, di antaranya, pengumpulan State report mereka kepada Human Rights Committee (HRC) sebagai treaty body dari ICCPR, dan untuk mematuhi rekomendasi yang dibuat oleh HRC kepada negara yang bersangkutan sebagai produk akhir dari proses eksaminasi State report yang bersangkutan. Kewajiban yang demikian diatur dengan harapan agar kepatuhan negara-negara anggota terhadap kewajiban-kewajiban perjanjian bisa dipastikan. Namun demikian, berdasarkan penilaian dari HRC sendiri, sebagaimana terefleksikan dalam concluding observation mereka terhadap State report pertama Indonesia, terdapat beberapa isu yang menunjukkan kegagalan Indonesia dalam memenuhi kewajiban ICCPR mereka yang, hingga saat penulisan artikel ini, masih bertahan. Artikel ini bertujuan untuk membahas mengenai faktor-faktor yang mungkin merupakan penyebab dari kegagalan-kegagalan tersebut, dan menemukan bahwa terdapat setidaknya dua faktor, yakni perluasan kewajiban perjanjian yang tidak sah oleh HRC itu sendiri, dan halangan yang lebih bersifat pragmatis dalam bentuk keengganan politis dari Indonesia untuk mengikuti rekomendasi oleh HRC karena kurangnya keinginan internal serta tekanan eksternal.